Facebook shaming as a tool to reduce crime in Malaysia: Evaluating effect and impact - Ismail, Shahrul Mizan (2014)
‘Shaming’ and ‘public humiliation’ has long been an equivocal tool of criminal justice and has been carried on as a form of ‘punishment’ by state authorities and members of the public, in a variety of ways in many parts of the world. However, since the latter part of the 20th century, humiliation has become amplified through the emergence of internet technology. The advent of social media has brought with it, the possibility of a cheaper and more convenient way of publicly humiliating a criminal offender. In fact, the relevant authorities are found to be increasingly using social media to find and monitor these offenders. Social media has now provided the society an instant avenue to bypass the justice system, and immediately imposes its own punishment which can become a weapon of mass reputation destruction, capable of amplifying shaming and public humiliation on a scale never before possible. This study aims at extrapolating the relationship between the influx of social media and the emergence of the modern day version of shaming and public humiliation as a form of ‘punishment’. It shall also assess the impact of this phenomenon on the Malaysian society and evaluate its effectiveness in controlling crimes in Malaysia. Since Malaysia is one of the countries in the world with the highest number of social media users, this research will indubitably contribute in providing a better understanding of the issues involved so that a more effective approach can be adopted in regulating the problem